2015
DOI: 10.1530/joe-15-0173
|View full text |Cite
|
Sign up to set email alerts
|

Macronutrients and caloric intake in health and longevity

Abstract: Both lifespan and healthspan are influenced by nutrition, with nutritional interventions proving to be robust across a wide range of species. However, the relationship between nutrition, health and aging is still not fully understood. Caloric restriction is the most studied dietary intervention known to extend life in many organisms, but recently the balance of macronutrients has been shown to play a critical role. In this review, we discuss the current understanding regarding the impact of calories and macron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
71
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 121 publications
(77 citation statements)
references
References 121 publications
(164 reference statements)
1
71
0
5
Order By: Relevance
“…The data convincingly showed that the key factor driving the survival effect was the protein to carbohydrate ratio, not the calories. The same group recently reported that short-term exposure to three of the previously reported diets under AL and CR conditions led to a metabolic impact of CR on glucose homeostasis that was very similar to the AL group fed a low protein diet, and that CR plus the low protein diet did not add further benefit than CR alone (Solon-Biet et al, 2015). …”
Section: What Role Does Dietary Composition Play?mentioning
confidence: 93%
See 1 more Smart Citation
“…The data convincingly showed that the key factor driving the survival effect was the protein to carbohydrate ratio, not the calories. The same group recently reported that short-term exposure to three of the previously reported diets under AL and CR conditions led to a metabolic impact of CR on glucose homeostasis that was very similar to the AL group fed a low protein diet, and that CR plus the low protein diet did not add further benefit than CR alone (Solon-Biet et al, 2015). …”
Section: What Role Does Dietary Composition Play?mentioning
confidence: 93%
“…We have already covered in the previous sections some of the differential physiological responses that distinguish CR from protein restriction (PR) and other aspects of diet composition. The impact of various feeding regimens were recently extensively reviewed (Le Couteur et al, 2016a; Le Couteur et al, 2016b; Masoro, 2005, 2006; Solon-Biet et al, 2015; Speakman and Mitchell, 2011; Speakman et al, 2016). The role of optimal dietary composition for promoting lifespan extension in ad libitum or CR condition remains unknown.…”
Section: What Role Does Dietary Composition Play?mentioning
confidence: 99%
“…The positive relationship between the concentration of protein in the experimental diets and protein intakes suggests that the strong regulation of protein is not absolute; rather, high concentrations of fats and carbohydrates restricted protein intake to some extent, whereas low concentrations resulted in compensatory responses leading to excess protein intake, but to a lesser extent than protein influenced carbohydrate and fat (Figure 3) and total energy intake (Figure 2b). Given recent evidence relating high protein intakes to accelerated rates of aging and poor latelife cardiometabolic health, especially when coupled with low carbohydrate intakes (83,91,92), this analysis suggests that the interaction of appetite systems for protein, fats, and carbohydrates might provide a fundamental mechanism underlying the reason that AMDRs have both an upper and lower protein limit. The analysis also shows why high-protein diets (Figure 5), although effective for weight loss through limiting energy intake (Figure 2b) as a result of protein feedbacks (Figure 3), have been associated with unhealthy metabolic profiles and premature death (83,89).…”
Section: Figurementioning
confidence: 99%
“…Longevity-promoting genes include components of the insulin-like signaling pathway, the histone deacetylase Sir2, the GTPase Ras, TRP membrane channels, and transcription factors, among many others (1,2). Environmental manipulations extending life include changes in nutrition (often referred to as caloric or dietary restriction), sexual/reproductive history, and ambient temperature (3)(4)(5).…”
mentioning
confidence: 99%